Basement-involved deformation overprinting thin-skinned deformation in the Pampean flat-slab segment of the southern Central Andes, Argentina - Japas, Maria Silvia (2016)
In the southern Central Andes, the Andean foreland was deformed due to Neogene shallowing of the Nazca slab beneath the South America plate. In this 27-33° S Pampean flat-slab segment, the N-trending Argentine Precordillera transpressional fold-and-thrust belt and the Sierras Pampeanas broken foreland developed as a consequence of inward migration of the orogenic front. At 28° S, a NNE-trending westward-dipping, thick Neogene synorogenic sequence is exposed in the Sierra de los Colorados, which shares deformation features of the Precordillera and the Sierras Pampeanas. Integration of new structural and kinematic data and available structural, kinematic, geophysical and palaeomagnetic information allows consideration of the Sierra de los Colorados area as part of the northern sector of the Precordillera during the middle Neogene. At c. 9 Ma, basement block exhumation started with the uplift of the Sierra de Umango-Espinal that was triggered by deformation along the NE-trending Tucumán oblique belt. This stage marked the beginning of compartmentalization of the incipiently deformed Vinchina foreland. Since c. 6.8-6.1 Ma, basement block uplift linked to the Miranda-Chepes and Valle Fértil NNW-trending sinistral transpressional belts, as well as kinking of the Neogene sequence by localized WNW-striking cross-strike structures, resulted in multiple segmentation that produced a complex mosaic of basement-block pieces. The overprint of these regional, basement-involved, oblique, brittle-ductile transpressional and cross-strike megazones could be related to high interplate coupling. Localized mechanical and rheological changes introduced by magmatism favoured this thick-skinned deformation overprint.